DISTRIBUTION PATTERN AND DIVERSITY OF EPIPHYTIC ORCHIDS IN THE CURUG CIBEREUM PATH, MOUNT GEDE PANGRANGO, INDONESIA - Bela Prapitasari; Ardyan Pramudya Kurniawan (BIOTROPIA, 2022)
The Curug Cibereum path as a tourist attraction in the Mount Gede Pangrango area is dominated by a lush tree, making it a suitable place to find a diversity of epiphytic orchids. This study aimed to determine the distribution pattern and diversity of epiphytic orchids along the Curug Cibereum path which is influenced by environtmental parameters. The research method was carried out by plotting ten plots on the right and left sides of the path, with each plot measuring 500 x 5 m and the distance between plots was 100 m. The results showed that there were 31 species of epiphytic orchids from 12 genera. The distribution pattern of epiphytic orchids was mostly clustered except for Oberonia lotsyana, which had a uniform pattern. The epiphytic orchid species with the highest INP were Bulbophyllum gibbosum with an INP value of 35% and Coelogyne speciosa with an INP value of 20%. Species diversity (H ') was moderate (H '=2.54), the evenness index (E) was high (E=0.73), the dominance index (D) was low (D=0.13). The measurements of environmental parameters showed optimal conditions for the growth of epiphytic orchids, namely with a temperature of 24.5 oC, soil moisture of 76.5%, air humidity of 70%, pH 5.1, the light intensity of 6351 lux and wind speed of 0.03 m/s.